THE EFFECT OF ICE CUBES THERAPY EDUCATION ON THIRST AND INTERDIALYTIC WEIGTH GAIN IN CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS AT BALARAJA HOSPITAL - Dava Rahmat Hidayat; Nabella Ayu Jeihan Fadhila (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2025)
Background: Chronic Kidney Failure (CKF) is a problem in the body's kidney function that makes it difficult to maintain metabolic processes, fluid balance, as well as electrolytes, which leads to increased urea levels. The main problem of chronic kidney failure patients undergoing hemodialysis is thirst and increased Interdialytic Weight Gain (IDWG), in the days between dialysis sessions the patient can experience problems with fluid accumulation in the body. One way to prevent this from happening is with ice cube therapy, so that patients can control fluid intake and its impact during two dialysis. Purpose of the study: To determine the effect of ice cubes therapy education on thirst and interdialytic weigth gain in chronic kidney failure patients undergoing hemodialysis at Balaraja Hospital. Research Method: The method used in this study is a quasy experiment with a pre and post design with control group. The sampling method in this study is purposive sampling. The sample used in this study was 30 respondents. The instruments in this study are ice cubes, coolboxes, weight scales, ice cube therapy education SAP, thirst observation sheet, interdialytic weight gain observation sheet. Research Results: The results of the independent sample test obtained a P value of 0,000 for thirst and 0,008 for interdialytic weight gain less than a significant value (a=0,05). Conclusion: The results of this study show that there is an effect of ice cubes therapy education on thirst and interdialytic weigth gain in chronic kidney failure patients undergoing hemodialysis.